Deconstructing reconciliation: What does it mean to reconcile former adversaries? - Čorkalo Biruški, Dinka (Array, 2009)
Intergroup reconciliation has been described as comprising characteristics such as re-humanization of the former adversary, dignity, trust, truth, emotional relation, justice, security, cooperation, etc. Reconciliation includes transforming the socio-psychological framework which is burdened by past wrongdoings and suffering into positive and collaborative, trusting and mutually agreeable relationship by the majority of members of the advisory groups. The key question that we want to address is: When is intergroup reconciliation possible? We will argue why instead of reconciliation in post-conflict settings we prefer the concept of social reconstruction as more adequate description of the real processes between former adversaries. We describe social reconstruction as a process within and around a community which brings its damaged social functioning to an improved level of interpersonal and groups relations and renews the community social fabric. Concepts of forgiveness, apology, reconciliation and the role of massive traumatization will be examined in the context of social reconstruction ; however their intrapersonal nature will be emphasized and their usefulness for the management of post-conflict group tensions will be reconsidered. Based on Nadler’s (2002) concept of instrumental and socioemotional aspects of reconciliation and our own understanding of the social reconstruction (Ajdukovic, 2004 ; 2005), Corkalo (2002), Ajdukovic & Corkalo (2004), we have developed the Social Reconstruction Scale. We will show that cooperation as an instrumental aspect of post-conflict social recovery is independent from more emotional aspects of social relations, which we call socioemotional approachment to the out-group. Implications for the future intergroup relation in the post-conflict community will be discussed.